Use of Delayed Cord Clamping in Preterm Dichorionic Twin Gestations [27B]. (May 2017) - Liu, Lilly; Grobman, William; Yee, Lynn
Abstract : INTRODUCTION: Delayed cord clamping (DCC) for premature neonates has become standard of care in singleton gestations, but the outcomes after DCC in twin gestations are unclear. The aim of this study was to examine feasibility and outcomes associated with DCC in twins. METHODS: This is a retrospective cohort study of women delivering dichorionic-diamniotic twin gestations between 23-32 weeks gestation at a single center (2013-2015). In 6/2013, this institution introduced a DCC protocol for singleton neonates delivering < 32 weeks, with some dichorionic twins who also received DCC. Clinical characteristics and neonatal outcomes of twins receiving DCC were compared to those who did not. Bivariable assessments and fixed effects multivariable logistic and linear regression were utilized. RESULTS: Of 58 women delivering dichorionic twins < 32 weeks, 8 (13.8%) had both neonates receive DCC, resulting in 16 neonates who received DCC. DCC occurred both among those who were delivered vaginally (n=7), and by cesarean section (n=9). Neonates who received DCC, compared to those who did not, had similar umbilical artery pH, initial temperature, 5-minute Apgar score, and peak bilirubin. Additionally, there were no differences in neonatal intensive care unit length of stay, birth hematocrit, total number of blood transfusions or transfusions received in the first week, mechanical ventilation, need for pressors, death, or other adverse outcomes. CONCLUSION: Performance of DCC in dichorionic twin gestations born < 32 weeks is feasible and not associated with worse neonatal outcomes in this small cohort. Further investigation of expansion of DCC protocols to dichorionic twin gestations appears worthy of exploration.